Deference to the Teacher in Salaf Pesantren: Between Theological Tradition, Social Habitus, and the Challenges of Modernity (A Case Study at Pesantren Salaf Al Ma'ruf, Kediri, East Java) - M Akhsanudin (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
Reverence, the practice of profound respect and moral submission to one's teacher, is one of the most distinctive and enduring features of the Salaf Islamic boarding school tradition in Indonesia. However, despite its cultural significance, Reverence has received insufficient theoretical attention in the sociology of Islamic education. This study uses a qualitative case study design to examine how Reverence is theologically grounded, socially transmitted, and culturally negotiated in Salaf Islamic boarding schools in East Java. Data were collected through in-depth interviews with kiai (Islamic scholars), senior ustadz (Islamic teachers), and students from various generations, non-participatory observation, and systematic document analysis. The findings are organized around three interrelated dimensions: (1) Reverence as a practice that is both theological and cultural, rooted in classical Islamic texts such as Al-Zarnuji's Ta'lim al-Muta'allim and Al-Ghazali's Ihya 'Ulum al-Din, expressed through a rich repertoire of bodily, verbal, and spatial rituals; (2) the social mechanisms through which Respect is transmitted and reproduced in Islamic boarding schools, analyzed through Bourdieu's concepts of habitus, field, and capital; and (3) the tensions and negotiations surrounding Respect in the context of modernity, digital culture, and the democratization of Islamic knowledge. This study finds that Respect is not simply a residual pre-modern habit, but a living, contested, and generative moral practice that performs crucial functions in the reproduction of Islamic scholarly authority and the formation of the identity of Islamic students.